Pengaruh Berbagai Jenis Bokasi dan Dosis Terhadap Perubahan Status Hara Makro (N, P dan K) Tanah Salin dan Pertumbuhan Tanaman Jagung (Zea mays L) - Manfarizah Manfarizah (Jurnal Agrista, 2006)
Effect of various Types of Bokasi and Dosages on the Change of Macro Nutrient (N, P and K) on Saline Soil and the Grewth of Maize (Zea mays L)ABSTRACT. The research was aimed to find out the effect of various types of bokasi and dosages on the change of macro nutrient (N, P and K) on saline soil and the growth of maize. The research method was a randomized complete block design factorial, consist of two factors. First factor was types of bokasi made from some organic matters decomposited using EM4 I,e. paddy hay, sawdust, and gamal. Second factor wa dosage I.e. 10 ton ha-1, 15 ton ha-1 and 20 ton ha-1. The experiment had three replications so that there were 27 experiment units. Observed variables were chemical soil properties (pH H2O, N total, P available, and K exchangeable at 60 days after incubation), plant growth (plant height at 30 and 60 days after planting, dry weight on top of plant and dry weight on the root at 60 days after planting. The result showed that application of various types of bokasi and dosage gave significant effect on al variable observed. Bokasi from gamal gave the biggest changes of all of observed variable, followed bay paddy hay and sawdust. The higher the bokasi dosage were given, the bigger the changes were occurred on all of observed variable. There were no significant interactions between bokasi types and dosage.